Automatic Compensation Device for Distribution Line Based on Wireless Sensor - Liu, Chunmei; Shi, Guohong (International Journal of Online and Biomedical Engineering (iJOE), 2017)
The purpose is to solve the problem that the automatic compensation device of the distribution line is too scattered. A power supply line automatic compensation device based on the wireless sensor network is proposed. The device data acquisition terminal adopts electromagnetic induction power supply and open wireless transmission design, without disconnecting the line threading and secondary lead to the controller. A more mature microcontroller is used as a controller, and it is combined with more advanced control algorithm and the reactive power of the electrical equipment in time, so as to detect and calculate the number of capacitor banks required for compensation. Based on the design of wireless sensor network, through the computer for real-time monitoring,the difficulties of promoting the automatic compensation of distribution lines due to the inconvenience of centralized operation and management have been overcome. In conclusion, the automatic compensation device can improve the quality of power supply and promote the development of China's electric power industry as long as it is continuously improved and perfected.